Examining job satisfaction through four (4) important facets of MSQ: A Study on employees at Zecon Berhad / Abdul Hadi Chee Mudin Chee - Mudin Chee, Abdul Hadi Chee (2019)
Because of its dynamic nature and expanding relations back and forth with other economic sectors, the construction sector play a significant and effective role. There is no denying that the construction sector is positively related to the success of every economy. This can be defined as a kind of economic engine for developing and developed countries. But, still there are certain issues of lack of job satisfaction among the construction workers with their current job which effect the lack of job performance, motivation of the workers, and increasing the employees turnover at the construction private company. Thus, in responding to lack of depth research on private sector staff especially in construction sector, this research aims to determine the influence of four (4) important facets of MSQ on job satisfaction among employees at Zecon Berhad. Generally, four (4) facets of MSQ are important for smooth functioning of an organization and satisfaction of employees and organization as whole that leads to determine the relationship between two variables (MSQ satisfaction facets and employee job satisfaction). The research design that is used in this study is descriptive research design. The study is focused at employees working at Zecon Berhad organization. The data are collected through structured questionnaire. The result of this study shows the findings may give input and believed to be significant and contribute further understanding about both variables in private sector.